UPAYA USAID MELALUI ESP DALAM MEMBANTU PENYEDIAAN AIR BERSIH DAN SANITASI DI INDONESIA - Simangunsong, Ray Jordy; Priadarsini, Ni Wayan Rainy; Fasisaka, Idin (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT Environmental issues has internationally become one of the main agenda. Enviromental damage on a large scale has become one of the main cause of the worsening of water quality sanitation in Indonesia. Regarding that issue, United States Agency For International Development (USAID) provide assistance to improve the clean water quality and sanitation in Indonesia through Environmental Service Program (ESP) . ESP has done a lot of efforts in restoring the quality of clean water and sanitation in Indonesia which can be shown by capacity growth, growth of environmental awareness, also policy advocacy . Other than that, throug h the ESP program USAID has also become a median between the local community and the government in their effort to improve the quality of clean water and sanitation . Key words: Clean water and sanitation,Environmental Service Program, Indonesia.